X+(x+3)=61

Simple and best practice solution for X+(x+3)=61 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+(x+3)=61 equation:


Simplifying
X + (x + 3) = 61

Reorder the terms:
X + (3 + x) = 61

Remove parenthesis around (3 + x)
X + 3 + x = 61

Reorder the terms:
3 + X + x = 61

Solving
3 + X + x = 61

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + X + -3 + x = 61 + -3

Reorder the terms:
3 + -3 + X + x = 61 + -3

Combine like terms: 3 + -3 = 0
0 + X + x = 61 + -3
X + x = 61 + -3

Combine like terms: 61 + -3 = 58
X + x = 58

Add '-1x' to each side of the equation.
X + x + -1x = 58 + -1x

Combine like terms: x + -1x = 0
X + 0 = 58 + -1x
X = 58 + -1x

Simplifying
X = 58 + -1x

See similar equations:

| 2x-4=3x+12 | | .06+.04x=18+.02 | | 8(b+7)=0 | | y=-4*-4+2*-4-7 | | 36y^7+4y^4= | | 4.5/g+2=3/0.5g-1 | | 12-5+x=5+8-2 | | 8x+2y+2=180 | | (2x+7)=87 | | 5d-4(d-9)=3d-(9-d) | | 3.5t+8=2.25t-16 | | 0.92x+.98(12-x)=.96(12) | | 3x^2-12x+165=180 | | y=-5*5+2*-3-7 | | 9n=3(n-2) | | 3x^2-12+165=180 | | 1-4x+4x^2=0 | | 2(3y-1)=-4 | | f=1.8x-11+32 | | F(9)=8 | | 3=3+-0.6 | | u^2-19u+90=0 | | X+30+63=180 | | 9a-25= | | 3x+15=2x-9 | | 5(b-4)=5b-2 | | 7y-4=7y+6 | | 0=3+-0.6 | | 28-x=-6(x-5)+5x | | 24=-8k-6k | | w+4W+12=13W+9 | | 6x-17x-28=0 |

Equations solver categories